A randomised controlled study of Bronchoscopic Lung Volume Reduction with endobronchial valves for patients with Heterogeneous emphysema and Intact interlobar Fissures : the BeLieVeR-HIFi study /: the BeLieVeR-HIFi study. (September 2015) - Zoumot, Zaid
No abstract available